پہوالی آزموندہ غا تا ادبی حیثیت: Literary Importance of Nomadic Customs in Ancient Brahui History - Hanfi, Muneer Ahmed (Al-Burz, 2013)
This research article discusses the importance of indigenous literature as a source of ancient Brahui history. The word "Pehvaali zind" in Brahui language describes a live hood of nomadic. Pehvaali zind is perfect in every dimension although no evidence of educational institute is found. A word Azmonda is used for such action which causes customs, or reflects tradition. Proverbs, riddles, Quotations and idioms shows the experiences and intellects of nomadic life. These all are have their social values and literary importance.